Diskriminasi dalam Pembangunan Eco City Terhadap Masyarakat Pulau Rempang - Rasyad, Pasha Athallah; Hadhani, Muhammad Gading Bintang; Tambunan, Daniel; Harley, Airiique Bintang Merah; Zulfikar, Faiz Raudhin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article discusses the discrimination that occurred on Rempang Island due to the construction of Eco City. This study was conducted to first find out the regulations on Land Use Authority in Batam City, especially Rempang Island, to find out the concept of legal protection for communities with land rights status in the Rempang Island area, and to find out how the government's development communication efforts are in handling this case. The method used in this article is a literature review, which is a systematic approach used to collect, analyze, and synthesize information from various sources that are relevant to the research topic. The results of this study indicate that there is a conflict between the Rempang Island community and the government regarding the construction of Eco City and how legal efforts and the government are to overcome this problem. From this conflict, development communication needs to be carried out effectively so that discrimination does not occur which results in conflict between indigenous peoples and the government.